Your Right to Pay Equity as a Registered Nurse - Slisarenko, Dana (Operating Room Nurses Association of Canada Journal, 1991)
Nursing is a highly undervalued resource of the health care system. Regardless of whether you are working as a registered nurse in hospital, industry, public health, education, management, research or as a nurse practitioner, you have the right to pay equity as a woman working as a registered nurse.